Antibacterial and Antioxidant Activities of Polyeugenol with High Molecular Weight - Erwin Abdul Rahim; Nur Istiqomah; Gilang Almilda; Ahmad Ridhay; Ni Ketut Sumarni; Indriani Indriani (Universitas Gadjah Mada, 2020)
This study was aimed to prepare polyeugenol with high molecular weight and to evaluate its antibacterial and antioxidant activities. First, polyeugenol was synthesized from eugenol in the presence of H2SO4-CH3COOH (4:1) as catalyst. The synthesized polyeugenol was weighed by using viscometer, revealing its high molecular weight of (7.76–21.9) × 105 g/mol. Furthermore, the antibacterial activity of the polyeugenol was conducted against Staphylococcus aureus and Escherichia coli bacteria. It was conducted by applying well diffusion method at 1, 2, 3, 4 and 5% concentrations to observe inhibition zones, in which the tests showed that the antibacterial activity of the polyeugenol against S. aureus were 17.42, 17.76, 18.79, 21.42 and 22.55 mm, while those against E. coli were 15.87, 17.23, 17.56, 18.24 and 19.21 mm, respectively. In short, these results indicated a strong antibacterial activity. Then, tests on antioxidant activity against free radical DPPH (2,2-diphenyl-1-pycrylhydrazyl) gave the IC50 value of 80.47 µg/mL, indicating a strong antioxidant activity. Therefore, the polymer synthesized in this work has a high potential to be applied in various biomedical applications.